Pentingnya Pengetahuan Ibu Mengenai Kebutuhan ASI Eksklusif Pada Bayi Usia 0 – 6 Bulan di Posyandu Kamboja Tukang Kayu Banyuwangi - Hidayatin, Nur; Hariani, Wahyu Fuji (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Mother's milk (ASI) is the first, main and best natural food for babies. Breast milk is a natural nutrient that has excellent nutritional value with a balanced composition and is in accordance with needs which is beneficial for the growth and development of babies aged 0 – 6 months. According to the World Health Organization (WHO), exclusive breast milk is breast milk given to babies aged 0-6 months without any additional food. Breast milk given to babies will be useful for preventing babies from various diseases, while for mothers it can prevent breast cancer. The aim of this community service is to provide information about the importance of mothers' knowledge regarding the need for exclusive breastfeeding for babies aged 0 - 6 months at the Cambodian carpenter posyandu Banyuwangi. This community service was carried out at the Cambodian carpenter Posyandu Banyuwangi using the counseling method for mothers who have babies aged 0 – 6 months. A total of 20 respondents. Most of them had knowledge in the good category. Counseling about exclusive breastfeeding is a form of providing education to every mother who has a baby or prospective mother